CIDP, myasthenia gravis, and membranous glomerulonephritis - three autoimmune disorders in one patient: a case report - Bolz, Saskia; Totzeck, Andreas; Amann, Kerstin Ute; Stettner, Mark; Kleinschnitz, Christoph; Hagenacker, Tim (BMC Neurology, 2018)
BACKGROUND: We present a patient fulfilling the electrophysiological criteria for definite chronic inflammatory demyelinating polyneuropathy (CIDP), antibody-positive myasthenia gravis (MG), and membranous glomerulonephritis (MGN) confirmed by biopsy. To our knowledge, this is the first case of the concomitant appearance of these three autoimmune diseases in a single patient. CASE REPRESENTATION: A 42-year-old Caucasian male presented with rapidly progressive gait disturbance, distal weakness of the lower extremities, ascending hypoesthesia, impaired fine motor skills, and beginning cranial nerve palsy showing dysarthrophonia, facial paralysis, and eye movement abnormalities and was diagnosed as rapid onset (atypical) CIDP. After 3 months, the patient complained of increasing physical exhaustion, reduction of his walking distance, worsening of the residual dysphagia, and dysarthria with an inability to swallow. AChR antibodies (17.0 nmol/L, RF < 0.4) and titin antibodies were positive and repetitive nerve stimulation showed an abnormal decrement matching the criteria of myasthenia gravis. Over time the patient developed severe acute-on-chronic renal failure with high-grade proteinuria resulting in generalized edema followed by secondary hyperparathyroidism and dialysis-dependent renal failure. Renal biopsy confirmed beginning anti-phospholipase A2 receptor antibody membranous nephropathy. CONCLUSION: All three diseases are of autoimmune origin with distinctive immunopathogenetic mechanisms. The present case of CIDP, MG, and MGN occurring in one patient indicates a common underlying immune mechanism in these distinct conditions, including the involvement of autoantibodies and T cells.
EVALuna2:205570